One-year results of two-site trabeculotomy in paediatric glaucoma following cataract surgery - El Sayed, Yasmine M. (Eye (Lond), 2020)
PURPOSE: The management of glaucoma following cataract surgery (GFCS) in children is challenging. This study looks at the results of two-site trabeculotomy in paediatric aphakic/pseudophakic glaucoma, 1-year post operatively. METHODS: This prospective, institutional study was performed on 33 eyes with GFCS in patients aged ≤14 years. Patients underwent two-site trabeculotomy using the rigid-probe trabeculotome, through a superonasal and an inferotemporal scleral flap. Intraocular pressure (IOP), medications, complications and success rates at 1 year were reported. Success was defined as IOP < 23 mmHg or 30% IOP reduction, on the same or fewer number of medications at 1 year, without the need for another glaucoma procedure. RESULTS: Trabeculotomy was performed on average 3.5 years after the cataract surgery. Patients were aged 5.73 ± 1.79 years. We excluded four eyes in which >180° incision could not be achieved. A 360° incision was achieved in 14 eyes (48%). There was a significant reduction in IOP and medications at 1, 3, 6 and 12 months (p < 0.001). At 1 year, mean IOP reduction was 48.2 ± 31.5%. Success was achieved in 26 eyes (89.6%), of which 15 were controlled without medications. There was no significant difference in IOP, medications or success between aphakic and pseudophakic eyes nor between eyes that had 360° trabeculotomy and eyes that had a 180–270° incision. Three eyes (10.3%) required another glaucoma procedure. One eye required core vitrectomy for vitreous haemorrhage. CONCLUSIONS: Two-site trabeculotomy can be used as an effective and safe first-line procedure in paediatric GFCS eyes that do not have extensive peripheral anterior synechiae.